2018
DOI: 10.1111/ajt.14611
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel factors are associated with immunosuppressant nonadherence in heart transplant recipients: The international BRIGHT study

Abstract: Factors at the level of family/healthcare worker, organization, and system are neglected in medication nonadherence research in heart transplantation (HTx). The 4‐continent, 11‐country cross‐sectional Building Research Initiative Group: Chronic Illness Management and Adherence in Transplantation (BRIGHT) study used multistaged sampling to examine 36 HTx centers, including 36 HTx directors, 100 clinicians, and 1397 patients. Nonadherence to immunosuppressants—defined as any deviation in taking or timing adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(126 citation statements)
references
References 63 publications
5
100
3
Order By: Relevance
“…This study used data from the Building Research Initiative Group: Chronic Illness Management and Adherence in Transplantation (BRIGHT) study (ClinicalTrials.gov ID: NCT01608477), a cross‐sectional study assessing healthcare providers’ practice patterns and the prevalence and variability of nonadherence to the post‐HTx treatment regimen in 36 HTx centers from 11 countries in Asia, Europe, North America, and South America.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study used data from the Building Research Initiative Group: Chronic Illness Management and Adherence in Transplantation (BRIGHT) study (ClinicalTrials.gov ID: NCT01608477), a cross‐sectional study assessing healthcare providers’ practice patterns and the prevalence and variability of nonadherence to the post‐HTx treatment regimen in 36 HTx centers from 11 countries in Asia, Europe, North America, and South America.…”
Section: Methodsmentioning
confidence: 99%
“…HTx recipients were excluded if they had participated in adherence intervention research or drug trials during the 6 months prior to inclusion or if they had received professional support for medication intake. Detailed information on the methodology of the BRIGHT study is reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our study only measured perceived barriers based on patient perception. Emerging evidence has ascertained that multilevel influences exist including barriers at the provider, organizational, and policy level . These were not addressed in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…Psychometric evidence: Original English version: 5 of the original 10 items retained in a unidimensional scale, with a Cronbach's alpha of 0.82 (Denhaerynck et al, ). German and French version: No further information available…”
Section: The Studymentioning
confidence: 99%